Vascular endothelial dysfunction after anthracyclines treatment in children with acute lymphoblastic leukemia - Woo Jung Jang; Duk Yong Choi; In-Sang Jeon (Korean Pediatric Society, 2013)
PurposeAnthracyclines have been utilized in the treatment of children with acute lymphoblastic leukemia (ALL). Recent studies have shown that anthracyclines may induce toxicity in the vascular endothelium. This study was performed using brachial artery reactivity (BAR) to evaluate vascular endothelial function in ALL patients who were treated with anthracycline chemotherapy.MethodsWe included 21 children with ALL who received anthracycline chemotherapy and 20 healthy children. The cumulative dose of anthracyclines in the ALL patients was 142.5±18.2/m2. The last anthracycline dose was administered to the patients 2 to 85 months prior to their examination using BAR. The diameter of the brachial artery was measured in both groups using echocardiography, and BAR was calculated as the percentage change in the arterial diameter after release of the cuff relative to the baseline vessel diameter.ResultsIn the anthracycline-treated group, BAR was observed to be 3.4%±3.9%, which was significantly lower than that observed in the control group (12.1%±8.0%, P<0.05). The time elapsed after the last anthracycline treatment and the age at the time of treatment did not affect the change in BAR (P=0.06 and P=0.13, respectively).ConclusionThese results provided evidence that treatment of ALL patients with anthracycline results in endothelial dysfunction. A larger cohort study and a longer follow-up period will be required to clarify the relationship between endothelial dysfunction resulting from anthracycline treatment for childhood ALL and occurrence of cardiovascular diseases later in life.